Illumina MiSeq Sequencing Reveals Diverse Microbial Communities of Activated Sludge Systems Stimulated by Different Aromatics for Indigo Biosynthesis from Indole - Zhang, Xuwang; Qu, Yuanyuan; Ma, Qiao; Zhang, Zhaojing; Li, Duanxing; Wang, Jingwei; Shen, Wenli; Shen, E; Zhou, Jiti (PLOS ONE, 2015)
Indole, as a typical N-heteroaromatic compound existed in coking wastewater, can be used for bio-indigo production. The microbial production of indigo from indole has been widely reported during the last decades using culture-dependent methods, but few studies have been carried out by microbial communities. Herein, three activated sludge systems stimulated by different aromatics, i.e. naphthalene plus indole (G1), phenol plus indole (G2) and indole only (G3), were constructed for indigo production from indole. During the operation, G1 produced the highest indigo yield in the early stage, but it switched to G3 in the late stage. Based on LC-MS analysis, indigo was the major product in G1 and G3, while the purple product 2-(7-oxo-1H-indol-6(7H)-ylidene) indolin-3-one was dominant in G2. Illumina MiSeq sequencing of 16S rRNA gene amplicons was applied to analyze the microbial community structure and composition. Detrended correspondence analysis (DCA) and dissimilarity tests showed that the overall community structures of three groups changed significantly during the operation (P<0.05). Nevertheless, the bacteria assigned to phylum Proteobacteria, family Comamonadaceae, and genera Diaphorobacter, Comamonas and Aquamicrobium were commonly shared dominant populations. Pearson correlations were calculated to discern the relationship between microbial communities and indigo yields. The typical indigo-producing populations Comamonas and Pseudomonas showed no positive correlations with indigo yields, while there emerged many other genera that exhibited positive relationships, such as Aquamicrobium, Truepera and Pusillimonas, which had not been reported for indigo production previously. The present study should provide new insights into indigo bio-production by microbial communities from indole.